Design thinking new product development essentials from the PDMA - Luchs, Michael 1968-; Swan, Scott 1962-; Griffin, Abbie (John Wiley & Sons, Inc., 2016)
Develop a more systematic, human-centered, results-oriented thought process Design Thinking is the Product Development and Management Association's (PDMA) guide to better problem solving and decision-making in product development and beyond.